The Influence Of Celebrity Endorser, Perceived Quality, And Testimonials On Purchase Intention Of Hanasui Products In Surabaya - Restiatin Restiatin; R. Yuniardi Rusdianto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The focus of this research is to analyze the partial and simultaneous effects of celebrity Endorser Variables, Perceived Quality, and Testimonials on Purchase Intention of Hanasui local brand products among Surabaya City consumers. The sample consisted of 205 respondents selected through purposive sampling method with the criteria of knowing Hanasui products, at least 17 years old, and domiciled in Surabaya. The data analysis technique was carried out with multiple linear regression analysis tests with the help of SPSS version 26 software. The findings showed that simultaneously and partially, Celebrity Endorsers, Perceived Quality, and Testimonials had a positive and significant impact on Purchase Intention.